A Case Report of Ascaridiosis in a Wild Boar in Turkey - Eroksuz, Yesari; İncili, Canan Akdeniz; Karabulut, Burak; Eröksüz, Hatice (My University, 2020)
This case report revealed ascaridiosis and it’s related lesions in liver, lung, and intestinal lesions ina wild boar. Granulomatous enteritis together with adult parasitic larvae, and hepatic fibrosis due toparasitic migration routes and eosinophilic brochitis in the lungs were detected. As wild boars aresource of infection for humans and domestic animals, necessary sanitary measures must be takenand furthermore contact of wild boars to vegetable and animal production units and pasture shouldbe avoided.As a result, wild boar ascaridiosis and related lesions were demonstrated for the first time in Turkeywith this case report.
Keywords: Parazitoloji; Veterinerlik